Tradisi Pertuq Dalam Perspektif Budaya Lombok Sasak - Alfin Malik Ibrahim; Muhamad Rizki Alpiansyah (The Center for Language Development, Mataram State Islamic University., 2025)
This study examines the Pertuq Tradition in the perspective of Lombok culture. This study includes activities to identify the meaning contained in the pertuq tradition seen from the perspective of Sasak Lombok culture. This study attempts to uncover the history of the Pertuq tradition on Lombok Island. Then, how the development of the Paretuq tradition on Lombok Island and why the Pertuq tradition is still carried out by the Sasak community of Lombok Island. The results of this study are that: As one of the local wisdoms of the Sasak community, the pertuk tradition actually has Islamic values ??so that it cannot be immediately contradicted with Islamic law itself. This tradition contains an inner dimension, namely related to the supernatural and has relevance to Sufism. This tradition is also considered a form of application of Sufism in everyday life so that it is believed to be able to cure diseases or disorders that are supernatural. From another dimension, the term tawasul is also known. Tawasul is a means of connecting with the outside, especially related to the relationship to Allah subhanahu wa ta'ala. In the context of healing, it is actually a form of prayer to Allah subhanahu wa ta'ala by remembering the spirits or ancestors. In Islamic belief, the spirits or souls of the ancestors are actually still alive and can still communicate within supernatural limits. That is why it has a supernatural dimension and everything returns to the Almighty. In-laws are only a medium of tawasul by involving the spirits of the ancestors by remembering Allah subhanahu wa ta'ala.